The Mechanistic Target of Rapamycin (mTOR): Novel Considerations as an Antiviral Treatment - Maiese, Kenneth (Current neurovascular research, 2020)
Multiple viral pathogens can pose a significant health risk to individuals. As a recent example, the β-coronavirus family virion, SARS-CoV-2, has quickly evolved as a pandemic leading to coronavirus disease 2019 (COVID-19) and has been declared by the World Health Organization as a Public Health Emergency of International Concern. To date, no definitive treatment or vaccine application exists for COVID-19. Although new investigations seek to repurpose existing antiviral treatments for COVID-19, innovative treatment strategies not normally considered to have antiviral capabilities may be critical to address this global concern. One such avenue that may prove to be exceedingly fruitful and offer exciting potential as new antiviral therapy involves the mechanistic target of rapamycin (mTOR) and its associated pathways of mTOR Complex 1 (mTORC1), mTOR Complex 2 (mTORC2), and AMP activated protein kinase (AMPK). Recent work has shown that mTOR pathways in conjunction with AMPK may offer valuable targets to control cell injury, oxidative stress, mitochondrial dysfunction, and the onset of hyperinflammation, a significant disability associated with COVID-19. Furthermore, pathways that can activate mTOR may be necessary for anti-hepatitis C activity, reduction of influenza A virus replication, and vital for type-1 interferon responses with influenza vaccination. Yet, important considerations for the development of safe and effective antiviral therapy with mTOR pathways exist. Under some conditions, mTOR can act as a double edge sword and participate in virion replication and virion release from cells. Future work with mTOR as a potential antiviral target is highly warranted and with a greater understanding of this novel pathway, new treatments against several viral pathogens may successfully emerge.